Selection and Admixture in a Polytypic Aposematic Frog - Yeager, Justin; Derryberry, Graham E; Blum, Michael J; Richards-Zawacki, Corinne L (The American naturalist, 2023)
AbstractPhenotypic differentiation within polytypic species is often attributed to selection, particularly when selection might be acting on a trait that serves as a signal for predator avoidance and mate choice. We evaluated this hypothesis by examining phenotypic and genotypic clines between populations of the strawberry poison frog , a polytypic species that exhibits aposematic color pattern variation that is thought to be subject to both natural and sexual selection. Our aim was to assess the extent of admixture and to estimate the strength of selection acting on coloration across a region of Panama where monomorphic populations of distinctly colored frogs are separated by polymorphic populations containing both color variants alongside intermediately colored individuals. We detected sharp clinal transitions across the study region, which is an expected outcome of strong selection, but we also detected evidence of widespread admixture, even at sites far from the phenotypic transition zone. Additionally, genotypic and phenotypic clines were neither concordant nor coincident, and with one exception, selection coefficients estimated from cline attributes were small. These results suggest that strong selection is not required for the maintenance of phenotypic divergence within polytypic species, challenging the long-standing notion that strong selection is implicit in the evolution of warning signals.